PEMENUHAN HAK PENDIDIKAN ANAK DIDIK PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN ANAK - Widari, Tatik Mei (DiH: Jurnal Ilmu Hukum, 2012)
AbstractViolation much going against the rights of children, government attention is needed in the fulfillment of Human Rights on the right to education of children in Child Penitentiary. Embodiment of the fulfillment of the right to education in Child Correctional Institution is required to support the empowerment of human resources in the future as a pillar of development and life. Article 9 paragraph (1) of Act No. 23 of 2002 states that every child has the right to obtain education and teaching in the context of personal development and level of intelligence in accordance with their interests and talents. This is one of the fundamental importance of education of children in prisons who should still be considered by all parties, both government and society itself. The substance which covers the definition of child described in various laws and regulations vary nationally and internationally by the Convention on Rights of the Child among others, every human being under the age of 18 years unless another set that applies to children determined that early adulthood is achieved. Constraints faced in fulfilling Correctional Institution Children Educate Children education Correctional rights, namely the substance of the Act, the interests and obligations related institutions, students in prisons that are not motivated, infrastructure (facilities construction), Lecturer and staff, quality program development, cooperation and coordination, funding, child welfare and community. Keywrods : student in prisont, education right